Potentials, Challenges, and Genetic and Genomic Resources for Sugarcane Biomass Improvement - Kandel, Ramkrishna; Yang, Xiping; Song, Jian; Wang, Jianping (Frontiers in Plant Science, 2018)
Lignocellulosic biomass has become an emerging feedstock for second-generation bioethanol production. Sugarcane (Saccharum spp. hybrids), a very efficient perennial C4 plant with a high polyploid level and complex genome, is considered as a top-notch candidate for biomass production due to its salient features viz. fast growth rate and abilities for high tillering, ratooning, and photosynthesis. Energy cane, an ideal type of sugarcane has been bred specifically as a biomass crop. In this review, we described 1) biomass potentials of sugarcane and its underlying genetics, 2) challenges associated with biomass improvement such as large and complex genome, narrow gene pool in existing commercial cultivars, long breeding cycle, and non-synchronous flowering, 3) available genetic resources such as germplasm resources, and genomic and cell wall-related databases that facilitate biomass improvement, and 4) mining candidate genes controlling biomass in genomic databases. We extensively reviewed databases for biomass-related genes and their usefulness in biofuel generation. This review provides valuable resources for sugarcane breeders, geneticists, and broad scientific communities involved in bioenergy production.